Insecticidal activities of long pepper (Piper retrofractum Vahl) fruit extracts against seed beetles (Callosobruchus maculatus Fabricius, Callosobruchus chinensis Linnaeus, and Sitophilus zeamais Motschulsky) and their effects on seed germination - J. Pumnuan; D. Namee; K. Sarapothong; Thanaporn Doungnapa; S. Phutphat; Chutichot Pattamadilok; K. Thipmanee (Heliyon, 2022)
, respectively. Bruchid beetles presented significant response to ethanol, acetone and hexane extracts, whereas maize weevil showed relatively low responsibility. Film seed coating with hexane extract at 1% and 3% concentrations with six-month storage presented high insecticidal activity against bruchid beetles by more than 88% mortality but had low kill rates against maize weevil. The coated mung bean seeds presented non-seed germination effect, whereas high effect was observed on coated corn. Isolation of bioactive components demonstrated that there were 74 compounds, where pentadecane was the main compound. Film seed coating technology for mung bean seed preservation by using 1% hexane extract from long pepper fruit presented to be an extremely effective method to control bruchid beetles without any seed germination effect. It could serve as one of the green insecticides of the future.
Keywords: Insect Pest Control Strategies; Agricultural pest management studies; Essential Oils and Antimicrobial Activity